Seleção de genes HOUSEKEEPING para análise de PCR quantitativo do gene GSTM1 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Quantitative real-time PCR (qPCR) is a technique that combines the exponential amplification system of a DNA fragment with the capture of data at the moment the amplification reaction occurs by means of fluorescence measurements. The qPCR became one of the most widely used techniques when it comes to gene expression analysis because of its precision, wide dynamic range, sensitivity, reproducibility. When it’s compared the gene expression between different samples and / or tissues, it is paramount to consider the aspects of the experimental variation resulting from the amount of starting material, RNA extraction and reverse transcription efficiencies. In order to eliminate such variations it’s necessary to use a normalizing gene to ensure the accuracy of the levels of expression of the assay qPCR. Therefore, this study aims to select reference genes for gene expression analysis assays of the GSTM1 family gene. It was collected peripheral blood samples (5 mL) from exposed individuals and not exposed ones to Mercury (Hg). The RNA extraction was performed, then cDNA synthesis and qPCR for seven normalizing genes (ACTB, GAPDH, 18S, HPRT1, B2M, GUSB and TBP). For the analysis of normalization of the reference genes, It was applied the technique developed by Silver et al. (2016) called "gene pairs". The results of the present work demonstrate that the ACTB, GAPDH and B2Mgenes presented better stability to be used as reference genes for GSTM1 gene studies.
Keywords: PCR quantitativa; Genes normalizadores; GSTM1; CNPQ::CIÊNCIAS BIOLÓGICAS